Symbolic Interaction and the Art of Islamic Communication: A Strategic Approach to Education - Batubara, Hafsah Juni; Suhendri (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2025)
This article explores communication strategies based on symbolic interactionism theory in the context of Islamic values education, particularly in facing the challenges of modernisation and globalisation. In Islamic education, communication plays an important role as a means of conveying and internalising values that shape the character, ethics, and worldview of students. Using a literature review approach, this study analyses how symbolic interactionism, which focuses on meaning-making through social interaction, can be applied to develop effective educational communication strategies. The findings indicate that interpersonal communication, group discussions, and the use of digital media are the main strategies that align with the symbolic interactionism framework. This approach enables educators to connect meaningfully with students, taking into account their social backgrounds and individual identities. By emphasising symbols, shared meanings, and personal involvement, Islamic educators can foster a deeper understanding and stronger commitment to Islamic values. This approach not only supports character development but also prepares students to navigate the global world without losing their religious identity. This study underscores the importance of adaptive and value-based communication strategies in enhancing the relevance and impact of Islamic education in the contemporary era.